A Textbook Evaluation of 500 Vocabulary Words Kids Need to Know - Nurun Najiah; Sokhira Linda Vinde Rambe; Ida Royani (English Education : English Journal for Teaching and Learning, 2026)
This study evaluates the 500 Vocabulary Words Kids Need to Know English vocabulary book, used at Maahad Tahfiz Baitul Ehsan Maluri, Kuala Lumpur. The aim is to assess its content based on textbook evaluation criteria by McDonough, Shaw, and Tomlinson. The research identifies the book’s strengths and weaknesses using a qualitative content analysis approach. The primary data source is a bilingual (English-Malay) vocabulary book for beginner learners, evaluated using 18 criteria. Results show the book meets 14 criteria, featuring clear vocabulary organization, relevant visuals, and a neat layout. The content progresses from simple to complex, supporting gradual vocabulary acquisition. However, the book lacks an explanation of the author’s methodology and does not provide a teacher’s guide, limiting its effectiveness as a standalone teaching resource. The findings aim to help educators select materials that better suit students’ needs and offer a reference for evaluating similar textbooks in future educational settings.